Therapeutic Potential of Silodosin for Chronic Prostatitis: Efficacy and Safety Insights: Therapeutic Potential of Silodosin for Chronic Prostatitis - Niazi, Abdul Basit; Asif, Muhammad; Ahmad, Irfan; Abdullah, Wajid; Ashraf, Sana; Ghaffar, Sadia (Pakistan Journal of Health Sciences, 2024)
Chronic prostatitis is a common urological condition impacting men globally and poses a considerable clinical challenge due to its diverse symptoms and vague causes. The symptoms significantly affect patients' quality of life. Objective: To investigate the efficacy and safety of silodosin in men with chronic prostatitis who have not previously been treated with alpha-blockers for this condition. Methods: A quasi-experimental study was conducted from July 2022 to June 2023 at Niazi Welfare Foundation Teaching Hospital, Sargodha. Eighty-two patients with chronic prostatitis were treated with 4 mg of silodosin once daily and monitored for 12 weeks. Data collection commenced following IRB approval (NM&DC-IRB-43) and informed consent from all participants. Descriptive statistics were used to calculate the mean and standard deviation. Mean differences in NIH-CPSI score were computed through paired t-test at p-value < 0.05, using SPSS version 25.0. Results: Results show noticeable improvement in CP and NIH-CPSI scores following treatment. The change in symptoms of CP and NIH-CPSI score before and after silodosin indication were statistically significant (p < 0.05). Additionally, the treatment was well-tolerated, with minimum adverse events reported. Conclusions: Silodosin, a novel selective inhibitor of the α1A-adrenergic receptor, proved to be effective in treating chronic prostatitis without significant side effects.